Skeleton tracking using kinect sensors - Zulhakim Zainal (2017)
The ability to track the joints of a human body is useful for rehabilitation for both home and clinical settings and it can be done by using the Microsoft Kinect SDK. Unfortunately, most Kinect SDK applications or games are not developed for rehabilitation purposes. Thus, this project aims to provide a programme using the Microsoft Kinect SDK to cater for the elderly and people undergoing physiotherapy. Most of the elderly are weak and they do not have access to rehabilitation services. It is worse for those who suffer from diseases that render them physically incapable of travelling long distances for such rehabilitation services. In this study, a simple rehabilitation service has been developed using the Microsoft Kinect SDK that can be placed in homes, to facilitate simple exercises that for the elderly, especially those with movement disorders. A series of exercises have been implemented and it can be repeated to count the number of times a particular exercise has been done and can be reset to start again, according to the amount of rehabilitation needed. This is a way to use modern technology to benefit those in need of such services and are limited their homes.